Seismic behavior of prefabricated steel reinforced concrete shear walls with new type connection mode. (March 2022) - Fu, Yanqing; Fan, Guanlei; Tao, Lan; Yang, Yunjie; Wang, Jiachen
Abstract: This paper proposed a new connection mode of prefabricated steel reinforced concrete (SRC) shear wall. The vertical rebars inside the edge concealed columns of the prefabricated SRC shear wall were welded by lap welding, the section steels inside the edge concealed columns of the prefabricated SRC shear wall were welded by ending plates, and the connection of the wall panel in the middle part of the shear wall was realized through the bolt connection between the wall footing unit and the connecting steel plate. Then the concrete was finally poured in the connecting area of the edge concealed column of the shear wall. In order to study the seismic behavior of this new type prefabricated SRC shear walls, the pseudo-static test and nonlinear finite element analysis were carried out. At the same time, parameterized analysis was carried out on the key factors affecting the new type prefabricated SRC shear wall, including axial compression ratio, concrete strength grade, steel ratio of edge concealed columns, reinforcement ratio of vertical rebar section and thickness of connecting steel plate. The research results show that the failure mode of the new type prefabricated SRC shear wall is the same as that of the integrally cast SRC shear wall, and the seismic behavior and bearing capacity are slightly lower, but the difference is very small and in an acceptable range. The increase of axial compression ratio, concrete strength grade and steel ratio of edge concealed column will increase the bearing capacity of the new type prefabricated SRC shear wall, but at the same time, it will reduce the ductility of the new type prefabricated SRC shear wall. The reinforcement ratio of vertical rebar section and the thickness of the connecting steel plate have little effect on the mechanical performance of the new type prefabricated SRC shear wall. Finally, the reasonable value range of the key parameters affecting the mechanical performance of the new type prefabricated SRC shear wall and the calculation method of the shear capacity of the horizontal connection was proposed, which provided a basis for the subsequent design.